Implementation of oral anticoagulation treatment guidelines in patients with newly diagnosed atrial fibrillation. Issue 12 (29th May 2021) - Arbel, Anat; Abu‐Ful, Zomoroda; Preis, Meir; Cohen, Shai; Saliba, Walid
Abstract : Aims: Oral anticoagulants (OACs) are considered the mainstay in preventing stroke in atrial fibrillation (AF). OAC treatment remains suboptimal among AF patients, even after the introduction of direct oral anticoagulants (DOACs). We aimed to assess trends overtime and current implementation of OAC treatment guidelines in AF, using a large dataset of real world data from Israel. Methods: This is a retrospective cohort study that includes all adult members of Clalit Health Services, the largest healthcare provider in Israel, with newly diagnosed nonvalvular AF between January 2014 and December 2019 with CHA2 DS2 ‐VASc score ≥2. OAC treatment rates were calculated and multivariate regression models were used to identify predictors of OACs initiation. Results: Overall, 46 531 patients were included in the study. The 3‐months cumulative OAC treatment rates increased consistently over the years: 46.9% (95% confidence interval, 46.1–47.7%), 54.9% (54.1–55.6%) and 61.7% (60.9–62.4%) during 2014–2015, 2016–2017 and 2018–2019, respectively. DOACs constituted 51.3% of prescribed OACs in 2014–2015 and increased to 95.1% during 2018–2019. On multivariate analyses, the likelihood of OACs initiation among AF patients increased across the years and across higher socioeconomic classes, and was more likely among females, Jews, statins users and patients previously screened for colorectal cancer, but less likely among smokers and patients with impaired renal function. The likelihood of treatment increased with higher CHA2 DS2 ‐VASc score and decreased with higher HAS‐BLED score. Conclusion: Despite the increasing OAC treatment rates among high‐risk AF patients, mainly attributed to the expanding DOAC use, OAC treatment scope is still far from optimal.